(untitled) (Global Journal of Human-Social Science, 2025)
Based on Jos Miguel Wisnik s proposition that popular song is a way of thinking about the world and therefore a kind of Gay Science to use the term originally coined by Nietzsche this paper aims to analyse the song Borzeguim by Antonio Carlos Jobim in order to understand its potential for developing ecological sensitivity As theoretical framework I will use the proposals of Jos Miguel Wisnik and Luiz Tatit as well as the contributions of critics of Jobim s work such as the academic Andr Rocha L Haudenschild The main thesis I m trying to defend is that Jobim s songs have points of contact with concrete poetry with indigenous Brazilian rhythms inspired by the work of the master Villa-Lobos and with elements of popular culture indigenous mythology and sertaneja prophecy Borzeguim is the Jobinian way of thinking about the world through the lens of the imagination It s a warning and a lament for these times of environmental crisis